THE USE OF THE HEIR'S ASSETS FOR A KENDURI KEMATIAN ACCORDING TO THE VIEW OF ULAMA: Case Study of Sub-District Of Meranti, Asahan Regency - Syaiful Anwar; Ali Akbar (KABILAH : Journal of Social Community, 2022)
Abstract: This study aims to analyze the views of scholars in Meranti Village, Meranti District, Asahan District on the use of inheritance for a death feast. The method used in this research is field research methods to collect qualitative data. Research data collection is done through observation, interviews, and analysis of documentation. The data analysis technique was carried out through qualitative analysis because this study refers to the theories contained in the Koran and the opinions expressed by the scholars regarding the use of heirs' inheritance for death feasts. The results of this study indicate that in the Meranti sub-district, Asahan Regency, the use of heirs' inheritance that is not in accordance with Islamic teachings, for example, is used for a death feast which is considered a tradition. In Islam the tradition may be maintained if it does not conflict with Islamic teachings, but the death feast which is considered a tradition turns out to be contrary to the teachings of the Islamic religion which was perfectly brought by the Prophet Muhammad. However, this is also still happening among the people in Meranti Village, Meranti District, Asahan District. In the view of Islam, holding a death feast involving the property of the deceased, inheritance and property of orphans is not required but holding a spirit feast like the practice of some people in which the family of the dead provides food to those who visit it is not a mistake from the side of syarak, even considered as good deeds if the goal is to agree to pray and ask for mercy from Allah swt for the dead, on the condition that the feast is not held for riya purposes but sincerely because of Allah. Keywords: inheritance, Kenduri Kematian Views of the Islamic Ulema